2014
DOI: 10.1371/journal.pone.0108164
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Transient Receptor Potential Ankyrin 1 Ion Channel in the Inflamed Human and Mouse Colon and Its Protective Roles

Abstract: Transient Receptor Potential Ankyrin 1 (TRPA1) channels are localized on sensory nerves and several non-neural cells, but data on their functional significance are contradictory. We analysed the presence and alterations of TRPA1 in comparison with TRP Vanilloid 1 (TRPV1) at mRNA and protein levels in human and mouse intact and inflamed colons. The role of TRPA1 in a colitis model was investigated using gene-deficient mice. TRPA1 and TRPV1 expressions were investigated in human colon biopsies of healthy subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 96 publications
(98 reference statements)
6
130
1
Order By: Relevance
“…1), e.g. the serous acinar and ductal cells of the human submandibular gland, the gastrin and parietal cells of the stomach, the epithelial cells of the esophagus, stomach and ileum and the enteroendocrine cells, macrophages, CD4+ T cells and CD45+ cells in the gastrointestinal tract [53,60,62,63,64,65,66,67,68,69,70,71]. …”
Section: Localization Of Trp Channels In the Gutmentioning
confidence: 99%
“…1), e.g. the serous acinar and ductal cells of the human submandibular gland, the gastrin and parietal cells of the stomach, the epithelial cells of the esophagus, stomach and ileum and the enteroendocrine cells, macrophages, CD4+ T cells and CD45+ cells in the gastrointestinal tract [53,60,62,63,64,65,66,67,68,69,70,71]. …”
Section: Localization Of Trp Channels In the Gutmentioning
confidence: 99%
“…Recently, it has been reported that TRPA1 as well as TRPM7 is functionally expressed on macrophages [7]. In addition, the specific inhibitors of TRPM7 prevent the polarization of macrophages towards the anti-inflammatory M2…”
Section: Discussionmentioning
confidence: 99%
“…Of proinflammatory mediators initially induced by surgical incision, interleukin (IL)-1 plays a critical host defense role against S. aureus by enhancing neutrophil recruitment [6]. Proinflammatory mediators such as IL-1 and tumor necrosis factor (TNF) were also shown to be upregulated in a colitis model of TRPA1 −/− mice, independent of toll-like receptors [7]. In addition, oxygen partial pressure was found to regulate TRPA1 activation in sensory neurons [8], suggesting that neuronal TRPA1 regulates the changes in the local inflammatory responses dependent on the changes in tissue environ-ment that are likely to occur after a surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…A marked upregulation of PACAP (and of VIP) mRNA expression was shown in TRPA1 (transient receptor potential Ankyrin type 1) KO mice, while this was not observed in wild type controls [ 84 ]. Expression levels of VPAC2 and PAC1R mRNA were not altered, whereas that of VPAC1 was downregulated in TRPA1 KO mice 10 days following colitis induction [ 84 ]. An earlier study revealed that mice lacking the TRPV-1 (transient receptor potential cation channel subfamily V member 1) receptor exhibit a defect in PACAP expression.…”
Section: Effects Of Pacap In Large Intestinal Infl Ammationmentioning
confidence: 97%
“…Changes in PACAP and receptor expression were also demonstrated in dextran sodium sulfate (DSS)-induced colitis of mice. A marked upregulation of PACAP (and of VIP) mRNA expression was shown in TRPA1 (transient receptor potential Ankyrin type 1) KO mice, while this was not observed in wild type controls [ 84 ]. Expression levels of VPAC2 and PAC1R mRNA were not altered, whereas that of VPAC1 was downregulated in TRPA1 KO mice 10 days following colitis induction [ 84 ].…”
Section: Effects Of Pacap In Large Intestinal Infl Ammationmentioning
confidence: 99%